Real-Time 3D Reconstruction of UAV Acquisition System for the Urban Pipe Based on RTAB-Map - Xinbao Chen; Xiaodong Zhu; Chang Liu (Applied Sciences, 2023)
In urban underground projects, such as urban drainage systems, the real-time acquisition and generation of 3D models of pipes can provide an important foundation for pipe safety inspection and maintenance. The simultaneous localization and mapping (SLAM) technique, compared to the traditional structure from motion (SfM) reconstruction technique, offers high real-time performance and improves the efficiency of 3D object reconstruction. Underground pipes are situated in complex environments with unattended individuals and often lack natural lighting. To address this, this paper presents a real-time and cost-effective 3D perception and reconstruction system that utilizes an unmanned aerial vehicle (UAV) equipped with Intel RealSense D435 depth cameras and an artificial light-supplementation device. This system carries out real-time 3D reconstruction of underground pipes using the RTAB-Map (real-time appearance-based mapping) method. RTAB-Map is a graph-based visual SLAM method that combines closed-loop detection and graph optimization algorithms. The unique memory management mechanism of RTAB-Map enables synchronous mapping for multiple sessions during UAV flight. Experimental results demonstrate that the proposed system, based on RTAB-Map, exhibits the robustness, textures, and feasibility for 3D reconstruction of underground pipes.